(untitled) (Modern education and development, 2024)
It is known that almost the main part of the drugs produced in the pharmaceutical industry on a global scale is prepared from raw materials of medicinal plants. According to the World Health Organization (WHO), about 80 percent of the world’s population consumes plant products. Scientific research conducted by the authors was also aimed at obtaining an extract from the leaves of the peach tree, which is considered a medicinal plant in our country. During the study, the average amount of carotenoids in the leaves of the common peach was equal to 0.087% ± 0.006, and it can be concluded that these indicators allow the preparation of medicinal extracts from the common peach for medical use.